Sphingosine-1-Phosphate-Specific G Protein-Coupled Receptors as Novel Therapeutic Targets for Atherosclerosis - Yoh Takuwa; Kazuaki Yoshioka; Noriko Takuwa; Yasuo Okamoto; Fei Wang (MDPI AG, 2011)
Atherosclerosis is a chronic inflammatory process involving complex interactions of modified lipoproteins, monocyte-derived macrophages or foam cells, lymphocytes, endothelial cells (ECs), and vascular smooth muscle cells. Sphingosine-1-phosphate (S1P), a biologically active blood-borne lipid mediator, exerts pleiotropic effects such as cell proliferation, migration and cell-cell adhesion in a variety of cell types via five members of S1P-specific high-affinity G protein-coupled receptors (S1P1-S1P5). Among them, S1P1, S1P2 and S1P3 are major receptor subtypes which are widely expressed in various tissues. Available evidence suggest that S1P and HDL-bound S1P exert atheroprotective effects including inhibition of leukocyte adhesion and stimulation of endothelial nitric oxide synthase (eNOS) in endothelial cells (ECs) through the activation of Gi signaling pathway via S1P3 and probably S1P1, although there is still controversy. FTY720, the phosphorylation product of which is a high-affinity agonist for all S1P receptors except S1P2 and act as an immunosuppressant by downregulating S1P1 on lymphocytes, inhibits atherosclerosis in LDL receptor-null mice and apoE-null mice through the inhibition of lymphocyte and macrophage functions and probably stimulation of EC functions, without influencing plasma lipid concentrations. In contrast to S1P1 and S1P3, S1P2 facilitates atherosclerosis by activating G12/13-Rho-Rho kinase (ROCK) in apoE-null mice. S1P2 mediates transmigration of monocytes into the arterial intima, oxidized LDL accumulation and cytokine secretion in monocyte-derived macrophages, and eNOS inhibition and cytokine secretion in ECs through Rac inhibition, NF-kB activation and 3'-specific phosphoinositide phosphatase (PTEN) stimulation downstream of G12/13-Rho-ROCK. Systemic long-term administration of a selective S1P2-blocker remarkably inhibits atherosclerosis without overt toxicity. Thus, multiple S1P receptors positively and negatively regulate atherosclerosis through multitudes of mechanisms. Considering the essential and multi-faceted role of S1P2 in atherogenesis and the impact of S1P2 inactivation on atherosclerosis, S1P2 is a particularly promising therapeutic target for atherosclerosis.